In-vitro and in-vivo respiratory deposition of a developed metered dose inhaler formulation of an anti-migraine drug - Ebtsam M. Abdou; Soha M. Kandil; Amany Morsi; Maysa W. Sleem (Taylor & Francis Group, 2019)
Enhancement of zolmitriptan bioavailability through development of micronized zolmitriptan pressurized metered dose inhaler (MDI) as an alternative to its traditional drug delivery systems. A reversed phase HPLC method for zolmitriptan determination was developed and evaluated. Micronized zolmitriptan MDI formulations were prepared using two different propellants. The prepared formulations were evaluated for mean shot weight, drug content, and leakage rate in addition to in-vitro deposition using next generation impactor where mass median aerodynamic diameter (MMAD), geometric standard deviation (GSD), fine particle dose, fine particle fraction (FPF), emitted dose (ED), and dispersibility were determined. The selected formulation was evaluated for in-vivo bronchial absorption in rats. The physicochemical characters of the prepared formulations were found to be dependent mainly on the vapor pressure of the used propellant. MDI formulation prepared with HFA 134a propellant was found to have the lowest MMAD (3.47 ± 0.65) with GSD of 2.3 ± 0.4. It also had the highest FPF (41.9), ED (89.26 ± 2.35) with dispersibility of 46.9%. This formulation, when applied to rats, resulted in faster Tmax (27 ± 5 min) with higher Cmax (1236 ± 116 ng/mL) and AUC(0-12) (3375 ± 482 ng/mL·h) over the oral tablet. Its relative bioavailability was 72.7% which was 1.25 times higher than the oral tablet relative bioavailability. Zolmitriptan MDI formulation was developed using micronized zolmitriptan powder without further modification or particle engineering. The developed formulation using HFA 134a propellant could be favorable alternative, with enhanced bioavailability, to zolmitriptan oral tablet for acute migraine treatment.